FOMO’s Impact on The Legal Sociology of Article 16, PMA No. 30/2024 in Banda Aceh - Bukhari Ali; Muhammad Husnul; Novi Heryanti; Ajidar Matsyah; Ahmad Fadhlan Afifi, Bukhari Ali, Muhammad Husnul Afifi (VRISPRAAK : International Journal of Law, 2026)
This study aims to analyze the phenomenon of FOMO (Fear of Missing Out) that affects the sociological aspects of law among the community regarding the implementation of Article 16 paragraph 1 of Minister of Religious Affairs Regulation No. 30 of 2024 in the selection of akad nikah venues in Banda Aceh City. It also examines the relationship between this factor and the low interest in choosing the Office of Religious Affairs (Kantor Urusan Agama) as the akad nikah venue, and compares it with venue choices not influenced by FOMO by observing the community’s low preference for the Office of Religious Affairs as the ceremony location. This research uses a descriptive qualitative approach with data collected through interviews and observations in three districts with the highest marriage registration numbers: Baiturrahman, Kuta Alam, and Lueng Bata. Respondents include brides and grooms, family members, and penghulus. The results show that the community is well informed about holding the akad nikah at the Office of Religious Affairs under Article 16 paragraph 1 of Minister of Religious Affairs Regulation No. 30 of 2024; however, the majority prefer to hold the akad nikah at three large mosques in Banda Aceh. The FOMO phenomenon has influenced the community’s cognitive patterns in choosing akad nikah venues, causing the beauty and luxury of the chosen locations to be prioritized. Differences in venue selection influenced by FOMO can be observed from cognitive considerations.